THE EFFECT OF BRAND IMAGE AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY (CASE STUDY AT REDDOORZ HOTEL NEAR BOTANI SQURE MALL BOGOR) - Ardani, Putri Aulia; Indriani, Putri (Akademi Komunitas MAPINDO, 2022)
ustomer loyalty is an impulse and consumer behavior to make purchases repeatedly and to build customer loyalty, it can be used as a very valuable asset for the company. This study aims to examine the effect of brand image and customer satisfaction on customer loyalty at Reddoorz Hotel Near Botani Square Mall, Bogor. The population in this study are consumers who visit Reddoorz Hotel Near Botani Square Mall, Bogor. And the sample used was 30 respondents based on the incidental sampling technique, that is, anyone who coincidentally met the researcher could be used as a sample. Research data was obtained from the results of distributing questionnaires to respondents. The analytical method used is multiple linear regression analysis with SPSS version 25. The results of the analysis show that the brand image variable (X1) has a positive and significant effect on customer loyalty (Y). However, the significance value of the customer satisfaction variable (X) does not affect customer loyalty (Y) at Reddoorz Hotel Near Botani Square Mall, Bogor, this means that H1 is accepted and H2 is rejected. Keywords: Brand Image, Customer Satisfaction, Customer Loyalty